Deciphering the biodiversity-production mutualism in the global food security debate - Seppelt, Ralf; Arndt, Channing; Beckmann, David; Martin, Emily A.; Hertel, Thomas W. (United Nations University, 2020)
Without large changes in consumption as well as sharp reductions of food waste and post-harvest losses, agricultural production must grow to meet future food demands. The variety of concepts and policies relating to yield increases fail to integrate an important constituent of production and human nutrition – namely biodiversity. We here develop an analytical framework to unpack this biodiversity production mutualism, which bridgesthe research fields of ecology and agro-economics. The analytical framework makes explicit the trade-off between food security and protection of biodiversity. In so doing, a route is sought to avoiding possible lock-ins of the global food system through over-intensification and to limiting further biodiversity loss through more comprehensive agro-ecosystem management. The framework suggests that, in low-input areas such as sub-Saharan Africa (SSA), the scope for increasing production is high, as is the scope for either damaging or preserving biodiversity. Landscape perspectives can help to realize this scope for production, especially in high potential regions such as Southern Africa, while preserving biodiversity.